Peatland Hydrology Analysis Using Rainfall and Water Table Level Approaches in the Riau Peat Hydrological Unit for the 2018-2020 Period - Putra, Raden; Adelheid, Jessica; L., Deni Okta; Mareta , Lesi (Indonesian Journal of Environmental Management and Sustainability, 2025)
Peat ecosystems are the world's largest carbon sink and are important in climate change mitigation and global environmental balance. However, tropical peat ecosystems, particularly in Riau Province, face serious threats due to anthropogenic activities such as land clearing, drainage, and plantation conversion. These activities are exacerbated by climate change, which causes a decrease in rainfall and increases the risk of peat fires. This study aims to analyze the relationship between rainfall and peat water level in the Riau Peat Hydrology Region (PHR) during the period from October 2018 to December 2020. The main data used are daily rainfall and peat water level data from 39 SIPALAGA stations owned by the Peat and Mangrove Restoration Agency (BRGM). Spatial data on peatland distribution and regional administrative boundaries were used to support the hydrological zone-based analysis. Statistical methods applied included correlation and coefficient of determination tests to evaluate the relationship between rainfall and peat water level. Daily data were accumulated monthly, and peat hydrological zones were identified based on the distribution of peatlands from the Ministry of Environment and Forestry (MoEF) Indonesia. The results showed that a decrease in rainfall significantly decreased peat water levels, with strong correlations in most hydrological zones. In addition, areas with intense drainage activities experienced a major shift from naturally flooded to drought-prone conditions, increasing the risk of fires. In contrast, significant rainfall only temporarily restores peat hydrological conditions. Spatially, some hydrological zones show different peat water table dynamics, depending on the intensity of rainfall and the level of anthropogenic disturbance. These findings make an important contribution to peat fire risk mitigation strategies and sustainable peat ecosystem management. By integrating temporal and spatial data, this research offers a comprehensive approach to support area-based peat protection policymaking, particularly in the face of climate change impacts and human activities.